Deep eutectic solvents as efficient solvent system for the extraction of κ-carrageenan from Kappaphycus alvarezii. (20th January 2016) - Das, Arun Kumar; Sharma, Mukesh; Mondal, Dibyendu; Prasad, Kamalesh
Graphical abstract: Three different deep eutectic solvents (DESs) prepared by the complexation of choline chloride with urea, ethylene glycol and glycerol along with their hydrated counterparts were used for the selective extraction of κ-carrageenan from Kappaphycus alvarezii, a red seaweed. Highlights: Hydrated and non-hydrated deep eutectic solvents (DESs) were employed to extract κ-carrageenan. The DESs were found to be suitable alternatives to the conventional extraction processes. Hydrated DESs were found to extract κ-carrageenan more efficiently. Abstract: Three different deep eutectic solvents (DESs) prepared by the complexation of choline chloride with urea, ethylene glycol and glycerol along with their hydrated counterparts were used for the selective extraction of κ-carrageenan from Kappaphycus alvarezii . Upon comparison of the quality of the polysaccharide with the one obtained using water as extraction media as well as the one extracted using widely practiced conventional method, it was found that, the physicochemical as well as rheological properties of κ-carrageenan obtained using DESs as solvents was at par to the one obtained using conventional method and was superior in quality when compared to κ-carrageenan obtained using water as solvent. Considering the tedious nature of the extraction method employed in conventional extraction process, the DESs can be considered as suitable alternative solvents for the facile extraction of the polysaccharide directly from the seaweed. However, among the hydrated and non-hydrated DESs, the hydrated ones were found to be more effective in comparison to their non-hydrated counterparts.